Disturbance Observer based Linear Feedback Controller for Compliant Motion of Humanoid Robot - Kim, Mingon; Kim, Jung Hoon; Kim, Sanghyun; Sim, Jaehoon; Park, Jaeheung (2018 IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION (ICRA), 2018)
Actuator modules of humanoid robots have relatively higher joint elasticity than those of industrial robots. Such joint elasticity could lead to negative effects on both the tracking performance and stability for walking. Especially, unstable contact between the foot and ground caused by joint elasticity is a critical problem, as it decreases the stability of position-controlled humanoid robots. To address this problem, this paper introduces a novel control scheme for position-controlled humanoid robots by which we can obtain not only enhance compliance capability for unknown contact but also suppress the vibration caused by joint elasticity. To estimate the disturbance caused by external forces and modeling errors between the actual system and nominal system, a disturbance observer based estimator is designed at each joint. Furthermore, a linear feedback controller for the flexible joint model and a gravity compensator is considered to reduce vibration and deflection due to the joint elasticity. The proposed control scheme was implemented on our humanoid robot, DYROS-JET, and its performance was demonstrated by improved stability during dynamic walking and stepping on objects.